2016
DOI: 10.11138/mltj/2016.6.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the cellular origin of rotator cuff muscle fatty infiltration and fibrosis after injury

Abstract: SummaryBackground: rotator cuff muscle atrophy, fibrosis and fatty infiltration are common complications after large and massive rotator cuff tears. Currently, there are no effective treatments for these muscle pathologies after injury. Furthermore, the cellular source for fibrotic and adipose tissues in rotator cuff muscle after injury remains unknown. In this study, we proposed that two groups of muscle resident progenitors, Tie2+ muscle mesenchymal progenitors and PDGFRα + fibro/adipogenic progenitor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 26 publications
6
98
0
Order By: Relevance
“…Fatty infiltration and fatty replacement are terms that describe processes by which tissue, generally exocrine tissue, is replaced in whole or in part by adipocytes [33, 34, 35]. Fatty infiltration of tissue is a normal part of the aging process, though pathological and accelerated forms can occur after tissue injury [36, 37]. Thymic involution, for example, is a systematic replacement of thymic tissue with adipocytes which occurs as an organism ages [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty infiltration and fatty replacement are terms that describe processes by which tissue, generally exocrine tissue, is replaced in whole or in part by adipocytes [33, 34, 35]. Fatty infiltration of tissue is a normal part of the aging process, though pathological and accelerated forms can occur after tissue injury [36, 37]. Thymic involution, for example, is a systematic replacement of thymic tissue with adipocytes which occurs as an organism ages [38].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty replacement due to soft tissue injury has been described in soft tissues (especially that of the rotator cuff [37]), traumatic bone injury [39] and in pancreatic injury due to primary duct stenosis or calcification [33, 34, 35]. In well-characterized rodent models of pancreatic duct ligation, the pancreatic tissue undergoes a series of predictable alterations.…”
Section: Discussionmentioning
confidence: 99%
“…, Pro‐Myogenic FAPs, Adipogenic FAPs ), dysfunction of FAP's could be implicated in all three detrimental changes in torn RC (muscle loss, fibrosis/stiffening, and fat accumulation). Indeed, the conditions under which FAPs take on an adipogenic fate exist in the inflammatory environment of the torn human RC, and a small animal model has shown potential for adipogenic differentiation of FAPs in the context of RC tear …”
Section: Multipotent Progenitors − Potential Sources Of Fat and Fibrosismentioning
confidence: 99%
“…used mouse RC muscles harvested at 2 and 6 weeks after unilateral massive RC tear surgeries to investigate the cellular origin of fatty infiltration. They demonstrated that the Tie2 + muscle mesenchymal progenitors are the major source of fibroblasts, while platelet‐derived growth factor (PDGF)‐α + fibro/adipogenic progenitor cells are the major source of adipocytes in RC muscle fatty infiltration …”
Section: Muscular Degenerationmentioning
confidence: 99%